Effects of dietary protein levels on growth performance and body composition of juvenile parrot fish, Oplegnathus fasciatus - Kang-Woong Kim; Mohammad Moniruzzaman; Kyoung-Duck Kim; Hyon Sob Han; Hyeonho Yun; Seunghan Lee; Sungchul C. Bai (International Aquatic Research, 2016)
Abstract The present study was conducted to evaluate the effects of dietary protein levels on growth, biometrics, hematology and body composition in juvenile parrot fish Oplegnathus fasciatus. Fish averaging 7.1 ± 0.06 g (mean ± SD) was randomly distributed into 15 net cages (each size: 60 × 40 × 90 cm, W × L × H) as groups of 20 fish. Five isocaloric diets (16.7 kJ/g energy) were formulated to contain crude protein levels (CP) as 35 (CP35), 40 (CP40), 45 (CP45), 50 (CP50) and 60 % (CP60) in the diets. Fish were fed one of the experimental diets at apparent satiation twice a day in triplicate groups. At the end of 8-week feeding trial, weight gain (WG) of fish fed with CP50 and CP60 diets were significantly higher than those of fish fed with CP35, CP40 and CP45 diets. Fish fed with CP45, CP50 and CP60 diets had higher feed efficiency (FE) and specific growth rate (SGR) than those of fish fed with CP35 and CP40 diets. Protein retention efficiency (PRE) decreased with increase of dietary protein levels among fish fed with the experimental diets. Whole-body crude protein and lipid contents increased with the dietary protein level up to CP50 diet. In conclusion, analysis of variance (ANOVA) revealed that the optimum dietary protein level could be 50 % for maximum growth of juvenile parrot fish, while the broken-line analysis of WG suggested that the level could be 48.5 %, in a diet containing 16.7 kJ/g energy.